Maternal high-fat diet alters angiotensin II receptors and causes changes in fetal and neonatal rats. Issue 5 (28th December 2018) - Xue, Qin; Chen, Fangyuan; Zhang, Haichuan; Liu, Yinghua; Chen, Pinxian; Patterson, Andrew J; Luo, Jiandong
Abstract: Maternal high-fat diet (HFD) during pregnancy is linked to cardiovascular diseases in postnatal life. The current study tested the hypothesis that maternal HFD causes myocardial changes through angiotensin II receptor (AGTR) expression modulation in fetal and neonatal rat hearts. The control group of pregnant rats was fed a normal diet and the treatment group of pregnant rats was on a HFD (60% kcal fat). Hearts were isolated from embryonic day 21 fetuses (E21) and postnatal day 7 pups (PD7). Maternal HFD decreased the body weight of the offspring in both E21 and PD7. The ratio of heart weight to body weight was increased in E21, but not PD7, when compared to the control group. Transmission electron microscopy revealed disorganized myofibrils and effacement of mitochondria cristae in the treatment group. Maternal HFD decreased S-phase and increased G1-phase of the cellular cycle for fetal and neonatal cardiac cells. Molecular markers of cardiac hypertrophy, such as Nppa and Myh7, were found to be increased in the treatment group. There was an associated increase in Agtr2 mRNA and protein, whereas Agtr1a mRNA and AGTR1 protein were decreased in HFD fetal and neonatal hearts. Furthermore, maternal HFD decreased glucocorticoid receptors (GRs) binding to glucocorticoid response elements at the Agtr1a and Agtr2 promoter, which correlated with downregulation of GR in fetal and neonatal hearts. These findings suggest that maternal HFD may promote premature termination of fetal and neonatal cardiomyocyte proliferation and compensatory hypertrophy through intrauterine modulation of AGTR1 and AGTR2 expression via GR dependent mechanism. Abstract : AGTR plays a vital role in maternal HFD-mediated cardiac changes in the developing heart, as a target of therapeutic intervention.